2004
DOI: 10.1002/jmv.20047
|View full text |Cite
|
Sign up to set email alerts
|

Regional outbreak of mumps due to genotype H in Korea in 1999

Abstract: Serological and virological studies were carried out of a mumps outbreak which occurred in one region, Yoeju County, Southeast of Seoul in Korea from September to December, 1999. Sera from 736 children at 8-13 years of age of patients with mumps and healthy children were tested for mumps-specific antibodies by enzyme immunoassay. The overall IgM positive rate was 7.6% (56/736), compared with 69.8% (514/736) for IgG. Of the 49 children with both IgG and IgM, 32 were also confirmed by both clinical and serologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
0
17
0
2
Order By: Relevance
“…Since this result fulfills the proposed criteria for assigning a new MuV genotype (15,41), it is plausible that Mongolian MuV sequences might be classified into a novel genotype. Meanwhile, the genotype H sequences of MuVs isolated in the late 1990s from Japan (SA475/JPN97) (37), Korea (Yeoju1498, Yeoju1502, Yeoju1503, and Yeoju1504) (19), and Switzerland (776273SHG and 776274SHG) (38), which were classified as members of subgenotype H2 (23,38), are included in the same branch with our new sequences, and the divergences among some of these sequences are not necessarily Ͼ5% (4.1 to 6.3%) (Fig. 2).…”
Section: Mumps Epidemics In Mongoliamentioning
confidence: 99%
See 1 more Smart Citation
“…Since this result fulfills the proposed criteria for assigning a new MuV genotype (15,41), it is plausible that Mongolian MuV sequences might be classified into a novel genotype. Meanwhile, the genotype H sequences of MuVs isolated in the late 1990s from Japan (SA475/JPN97) (37), Korea (Yeoju1498, Yeoju1502, Yeoju1503, and Yeoju1504) (19), and Switzerland (776273SHG and 776274SHG) (38), which were classified as members of subgenotype H2 (23,38), are included in the same branch with our new sequences, and the divergences among some of these sequences are not necessarily Ͼ5% (4.1 to 6.3%) (Fig. 2).…”
Section: Mumps Epidemics In Mongoliamentioning
confidence: 99%
“…Molecular phylogenetic analyses show that the Mongolia MuV sequences form a single cluster, and that these viruses are most closely related to a cluster of genotype H viruses, such as Japanese isolate (SA475/JPN97, isolated in 1997) (37), Korean isolates (Yeoju1498, Yeoju1502, Yeoju1503, and Yeoju1504, isolated in 1999) (18,19) and Swiss isolates (776273SHG and 776274SHG, isolated in 1999 and 2000) (38). These strains were all isolated within a relatively short time period, from 1997 to 2000, and their SH gene sequences are almost homologous at the amino acid level ( Table 2).…”
Section: Vol 49 2011 Mumps Genotype In Mongolia 1921mentioning
confidence: 99%
“…Finally, previous experience with the elimination programs for other preventable viral diseases, such as measles, rubella, and polio, suggest that genotyping would facilitate mumps surveillance (38), since the pattern of viral circulation can be traced. Consequently, molecular epidemiology studies have been performed around the world (2,7,10,11,12,15,17,18,23,31,32,33,34,35,41).Mumps vaccination was introduced in the Spanish national vaccination repertoire in 1981 as part of the triple viral vaccine (the MMR vaccine). As a result, the number of mumps cases fell from 286,887 in 1984 to 1,527 in 2004.…”
mentioning
confidence: 99%
“…It was first developed in 1999 by Jin et al (16), who also first identified the H genotype and found an isolate dating back to 1989 which belonged to this genotype. Since then, this genotype has been identified worldwide (4,16,19,32), but an outbreak as large as that described in our current report has never been associated with this genotype.…”
mentioning
confidence: 46%